Squamous Cell Carcinoma of the Scalp after Artificial Hair Implantation - Nakayama, Satoru (Plast Reconstr Surg Glob Open, 2021)
A 48-year-old man with a protruding tumor on the parietal region had undergone treatment of alopecia using artificial synthetic fibers 2 or 3 times a year for 10 years from 30 to 39 years old. Three months before the first consultation at our hospital, he noticed a small tumor that had gradually shown bleeding and discharge, with expansion of the affected area. A diagnosis of squamous cell carcinoma (SCC) was made based on a biopsy, and we resected the tumor with a 1-cm surgical margin from the reddened area around the protruding tumor (14 × 11 cm), including the periosteum membrane. No tight adhesion was found between the periosteum and skull, so we excised the outer table of the skull of the central part (diameter: 8 cm) for a pathological analysis. A pathological study showed moderately differentiated SCC with a negative surgical margin. The whole tumor was surrounded by scar tissue with buried artificial hair implants. The second surgery was performed on the 15(th) postoperative day. An anterolateral thigh flap was divided into 2 flaps to fit the circle-shaped wound. This is the second report of SCC developing after artificial hair implantation in the frontal-parietal scalp. The whole protruding tumor was surrounded by scar tissue with buried artificial hair implants. Proving the direct causal relationship between inflammation of scar tissue and SCC generation is difficult; however, our pathological findings support the possibility of the harmful effects of artificial hair implants.